Gogol's crime and punishment : an essay in the interpretation of Nikolai Gogol's Dead souls - Heftrich, Urs (Studies in Russian and Slavic literatures, cultures and history., 2022)
"This monograph is nothing less than a bold attempt at solving the riddle of Gogol's novel "Dead Souls" that even inspired a staging of "Dead Souls" at Schauspiel Stuttgart. Heftrich gives a comprehensive, coherent answer to the question of the novel's meaning by meticulously laying bare its structure. The first part of the monograph is dedicated to one section of Gogol's novel that has been neglected by virtually all critics - a clue that leads to a strictly ethical reading of Gogol's epic. Gogol, as it emerges, constructed "Dead Souls" strictly according to a moral pattern. It is amazing to discover how flawlessly "Dead Souls" is built in this regard. The novel thus proves to be a true descendant of medieval romance with its inseparable interrelation between ethics and epics"--